Xuezhikang Therapy Increases miR-33 Expression in Patients with Low HDL-C Levels. (23rd January 2014) - Cao, Ruihua; Bai, Yongyi; Sun, Lan; Zheng, Jin; Zu, Mian; Du, Guanhua; Ye, Ping
Abstract : Background . MicroRNA-33a and -b (miR-33a/b) have been revealed to be posttranscriptional regulators of HDL metabolism. Xuezhikang (XZK) is a marked natural HDL-raising polypill. We aim to evaluate the effects of XZK on the expression of circulating miR-33a/b in patients with low plasma HDL-C levels. Methods . A total of 42 participating patients with low baseline levels of HDL cholesterol were assigned to receive an XZK capsule, 600 mg twice daily for 6 months. The expression of circulating miR-33a/b was detected at baseline and after XZK therapy measured with quantitative reverse-transcription (RT) polymerase chain reaction (PCR). Results . The mean (SD) HDL-C level after XZK treatment was 1.19 (0.13) mmol/L, representing an increase of 11.2% from baseline (P < 0.001 ). Q-PCR analysis of plasma miRNAs revealed an increase in relative miR-33a/b expression with XZK treatment. The miR-33a expression was raised from 0.81 to 1.73 (P = 0.012 ); miR-33b expression was increased from 1.2 to 2.75 (P < 0.001 ). The changes of miR-33a and miR-33b were inversely related to the posttreatment LDL-C levels (r = - 0.37, P = 0.019 ;r = - 0.33, P = 0.035, resp.). Conclusion . In patients with low HDL-C levels, XZK therapy raised plasma levels of miR-33a and miR-33b, which may inhibit cellular cholesterol export and limit the HDL-raising effect of XZK.